Marcos regulatórios para as bibliotecas públicas no Brasil - Ramos, Marília Cossich (2017)
This research deals with the process of building legal frameworks for public libraries in Brazil. Its objective is to map the national legal frameworks for public libraries, with a focus on identifying and analyzing bills underway in the Chamber and the Federal Senate. It also aims to encourage the participation of librarians in the formulation of legislative proposals and the monitoring of society in the construction of legislation. It is an applied research, of qualitative and quantitative approach, of documentary nature. The research universe is the bills in progress in the National Congress. It was carried out in three stages, the first one for the bibliographical survey, the second one was for the survey and systematization of existing legislation at the federal level, and the third was the analysis of government proposals for public libraries. It presents reflections on the public policies and cultural policies that have been implemented by specialists in the area. It reports on the main programs of the federal government regarding Brazilian public libraries. It identifies, analyzes and discusses federal legislation, specifically laws, decrees and bills that have the public library as the focus, and proposes initiatives to broaden and motivate the participation of society in the construction of legal frameworks.